Prevention of biliary fistula after partial hepatectomy by transcystic biliary drainage: randomized clinical trial. Issue 7 (9th January 2020) - Maulat, C.; Regimbeau, J.‐M.; Buc, E.; Boleslawski, E.; Belghiti, J.; Hardwigsen, J.; Vibert, E.; Delpero, J.‐R.; Tournay, E.; Arnaud, C.; Suc, B.; Pessaux, P.; et al.
Abstract : Background: Biliary fistula is one of the most common complications after hepatectomy. This study evaluated the effect of transcystic biliary drainage during hepatectomy on the occurrence of postoperative biliary fistula. Methods: This multicentre RCT was carried out from 2009 to 2016 in nine centres. Patients were randomized to transcystic biliary drainage or no transcystic drainage (control). Patients underwent hepatectomy (more than 2 segments) of non‐cirrhotic livers. The primary endpoint was the occurrence of biliary fistula after surgery. Secondary endpoints were morbidity, postoperative mortality, duration of hospital stay, reoperation, readmission to hospital, and complications caused by catheters. Intention‐to‐treat and per‐protocol analyses were performed. Results: A total of 310 patients were randomized. In intention‐to‐treat analysis, there were 158 patients in the transcystic group and 149 in the control group. Seven patients were removed from the per‐protocol analysis owing to protocol deviations. The biliary fistula rate was 5·9 per cent in intention‐to‐treat and 6·0 per cent in per‐protocol analyses. The rate was similar in the transcystic and control groups (5·7 versus 6·0 per cent; P  = 1·000). There were no differences in terms of morbidity (49·4 versus 46·3 per cent; P  = 0·731), mortality (2·5 versus 4·7 per cent; P  = 0·367) and reoperations (4·4 versus 10·1 per cent; P  = 1·000). Median duration of hospital stay was longer in the transcystic group (11 versus 10 days; P  = 0·042). The biliary fistula risk was associated with the width and length of the hepatic cut surface. Conclusion: This randomized trial did not demonstrate superiority of transcystic drainage during hepatectomy in preventing biliary fistula. The use of transcystic drainage during hepatectomy to prevent postoperative biliary fistula is not recommended. Registration number: NCT01469442 ( http://www.clinicaltrials.gov ). Abstract : This RCT evaluated the effect of biliary drainage with a transcystic catheter during hepatectomy on the occurrence of postoperative biliary fistula. A total of 310 patients were randomized in nine centres; the analysis included 158 patients in the transcystic group and 149 in the control group. The biliary fistula rate was similar in the transcystic and control groups. Therefore, the use of transcystic drainage during hepatectomy to prevent postoperative biliary fistula is not recommended. Biliary drainage not of added value Abstract : Antecedentes: La fístula biliar es una de las complicaciones más comunes después de la hepatectomía. Este estudio evalúa el efecto del drenaje biliar transcístico durante la hepatectomía en la aparición de una fístula biliar postoperatoria. Métodos: Este ensayo prospectivo aleatorizado y multicéntrico (Clinical Trial NCT01469442) con dos grupos de estudio (grupo transcístico versus grupo control) se llevó a cabo de 2009 a 2016 en 9 centros. Los pacientes fueron sometidos a una hepatectomía (≥ 2 segmentos) en hígados no cirróticos. El resultado principal fue la aparición de una fístula biliar después de la cirugía. Los resultados secundarios fueron la morbilidad, la mortalidad postoperatoria, la duración de la estancia hospitalaria, la reintervención, la necesidad de reingreso y las complicaciones causadas por los catéteres. Se realizaron análisis por intención de tratamiento y por protocolo. Resultados: Un total de 310 pacientes fueron randomizados. Por intención de tratamiento, 158 pacientes fueron aleatorizados al grupo transcístico y 149 al grupo control. Siete pacientes fueron excluidos del análisis por protocolo por desviaciones del protocolo. La tasa de fístula biliar fue del 5, 9% en el análisis por intención de tratamiento y del 6, 0% en el análisis por protocolo. Esta tasa fue similar para el grupo transcístico y para el grupo control: 5, 7% versus 6, 0% ( P = 1). No hubo diferencias en términos de morbilidad (49, 4% versus 46, 9%, P = 0, 731), mortalidad (2, 5% versus 4, 7%, P = 0, 367) y reintervenciones (4, 4% versus 10, 1%, P = 1). La mediana de la duración de la estancia hospitalaria fue mayor para el grupo transcístico (11 versus 10 días, P = 0, 042). El riesgo de fístula biliar se correlacionó con el grosor y la longitud de la transección hepática. Conclusión: Este ensayo aleatorizado no demuestra la superioridad del drenaje transcístico durante la hepatectomía para prevenir la fístula biliar. No se recomienda el uso de drenaje transcístico durante la hepatectomía para prevenir la fístula biliar postoperatoria.